NILAI-NILAI PENDIDIKAN AKHLAK DALAM KITAB TAISIRUL KHALLAQ KARYA SYEKH HAFIDH HASAN AL-MAS’UDI - Herawati . (Program Studi Pendidikan Agama Islam, 2017)
Moral education is a very prioritized sequence in education, so it must be a priority goal that must be achieved by someone. This is because in the dynamics of this life, morality is the pearl of life that can distinguish humans from other God's creatures. The background of this research is the progress of technology and science that is growing very rapidly, thus making the era of globalization more modern full of sophistication. These technological advances do have a positive impact on humans, but also many negative impacts are obtained. This study aims to determine the values of moral education contained in the book Taisirul Khallaq and their relevance to moral education today. This research is a type of library research and the approach used is a qualitative approach. Data collection techniques used in the form of literature study and documentation. The data analysis technique used is content analysis, namely by analyzing the contents of the Taisirul Khallaq book. The results of this study indicate that the values of moral education in the Taisirul Khallaq book teach good attitudes and behavior, such as the morals of the Prophet Muhammad. And there are three aspects of value contained in the book. First, the value of moral education towards God. Second, the value of moral education for humans. Third, the value of moral education related to oneself. And its relevance to moral education today is very important to be applied in everyday life because it is expected to produce a generation of Muslims who have good and noble personalities